2019
DOI: 10.1111/acer.13997
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and Neuroimaging Examinations of Self‐Reported Sleep Quality in Alcohol Use Disorder With and Without Korsakoff's Syndrome

Abstract: 33Background: Alcohol Use Disorder (AUD) patients without Korsakoff's syndrome (KS) report a 34 variable self-rated sleep quality. Their ability to accurately judge their sleep quality may be related to 35 their alcohol-related cognitive deficits and brain damage. KS patients, who present severe brain 36 dysfunction, may be cognitively unable to judge their sleep quality. The aim of the present study is to 37 examine in AUD and KS patients, whether the absence of sleep complaint is associated with altered 38 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
3
8
0
Order By: Relevance
“…Our findings are consistent with the literature, although previous studies were generally conducted among populations suffering from alcoholism or alcohol abuse (11,29,30) . A recent large-scale study, including 151 567 adults with problematic alcohol consumption and post-traumatic stress disorder symptoms, found an inverse association between alcohol consumption and sleep quality (11) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with the literature, although previous studies were generally conducted among populations suffering from alcoholism or alcohol abuse (11,29,30) . A recent large-scale study, including 151 567 adults with problematic alcohol consumption and post-traumatic stress disorder symptoms, found an inverse association between alcohol consumption and sleep quality (11) .…”
Section: Discussionsupporting
confidence: 93%
“…A recent large-scale study, including 151 567 adults with problematic alcohol consumption and post-traumatic stress disorder symptoms, found an inverse association between alcohol consumption and sleep quality (11) . Another recent study, investigating the relationship between AUD, with and without Korsakoff's syndrome and sleep quality, showed that the sleep complaints were prevalent among the participants with AUD (29) . A longitudinal study with 696 adolescents (12-19 years old) found that insomnia and sleep problems may be a consistent problem for adolescents with AUD and may also be a risk factor for the development of AUD in adolescents (30) .…”
Section: Discussionmentioning
confidence: 99%
“…In AUD, a few studies reported that poor sleep quality is related to poor QoL [ 42 ] or is an important component of HRQoL [ 56 ]. The absence of relationship between sleep quality and HRQoL in our study could be explained by the fact that recently detoxified sAUD patients with executive deficits could not be cognitively able to accurately self-evaluate their sleep [ 57 ]. Further investigations using objective sleep measures are required to better understand the relationship between sleep and HRQoL in AUD.…”
Section: Discussionmentioning
confidence: 99%
“…In AUD, a few studies reported that poor sleep quality is related to poor QoL (42) or is an important component of HRQoL (56). The absence of relationship between sleep quality and HRQoL in our study could be explained by the fact that recently detoxi ed sAUD patients with executive de cits could not be cognitively able to accurately self-evaluate their sleep (57). Further investigations using objective sleep measures are required to better understand the relationship between sleep and HRQoL in AUD.…”
Section: -Discussionmentioning
confidence: 68%